1999
DOI: 10.1111/1468-0351.00033
|View full text |Cite
|
Sign up to set email alerts
|

Selected transition and Mediterranean countries: an institutional primer on EMU and EU accession

Abstract: The paper examines the institutional channels through which Economic and Monetary Union (EMU) in the European Union (EU) can affect the transition countries of Central and Eastern Europe and three Mediterranean countries that aspire to join the EU.After describing the current institutional framework for relations between the EU and these countries, the paper considers two categories of institutional implications of EMU. The first stems from the need to satisfy the Maastricht convergence criteria before joining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Even Romania's score was above the mid-point of his index's continuum. The International Monetary Fund (2000: 157) as well as Temprano-Arroyo and Feldman (1999) reported that all transition economies acceding to the EU had accepted Article VIII on current account convertibility and had removed most restrictions on transactions related to foreign direct investment. At the end of 1997, the Baltic countries had achieved nearly the maximum score on their capital account liberalization index, and the Czech Republic, Hungary and Poland were in the higher half of the index's range.…”
Section: Correlation Of Fiscal Positionsmentioning
confidence: 99%
“…Even Romania's score was above the mid-point of his index's continuum. The International Monetary Fund (2000: 157) as well as Temprano-Arroyo and Feldman (1999) reported that all transition economies acceding to the EU had accepted Article VIII on current account convertibility and had removed most restrictions on transactions related to foreign direct investment. At the end of 1997, the Baltic countries had achieved nearly the maximum score on their capital account liberalization index, and the Czech Republic, Hungary and Poland were in the higher half of the index's range.…”
Section: Correlation Of Fiscal Positionsmentioning
confidence: 99%
“…The agreement implementing the final phase of the CU became effective in December 1995. Accordingly, both parties have eliminated customs duties on industrial and processed goods (Temprano-Arroyo and Feldman, 1999). Since the CU agreement, Turkey has demonstrated the ability to cope with the competitive challenge of free trade.…”
Section: Turkey: the Eu The Emp And The Triple Logic In Actionmentioning
confidence: 99%
“…Since the CU agreement, Turkey has demonstrated the ability to cope with the competitive challenge of free trade. However, Turkey has been denied full membership in the EU on political and social grounds, including its human rights records, hostile relations with Greece over Cyprus, demographic characteristics and high population rate, and concerns over her "European" status (Temprano-Arroyo and Feldman, 1999 ).…”
Section: Turkey: the Eu The Emp And The Triple Logic In Actionmentioning
confidence: 99%
See 1 more Smart Citation